1162 Improved exercise tolerance and cardiac index at mid-term follow up after tricuspid valve surgery of Ebsteins anomaly. (17th January 2020) - Ostenfeld, E; Simard, F; Smith, G; Ghonim, S; Rydman, R; Pennell, D; Gatzoulis, M A; Li, W; Babu-Narayan, S V
Abstract: Funding Acknowledgements: Swedish Heart-Lung Foundation, Swedish Society of Medicine, Swedish Heart Association, Skåne University Hospital, Region Skåne, and Lund University Background: Ebstein's anomaly (EA) is due to failed delamination of the tricuspid valve (TV) causing TV regurgitation (TR) and right ventricular (RV) dilatation, reduced exercise capacity and survival. TV repair/replacement (TVR) aims to reduce morbidity and mortality by reducing regurgitation and RV dilatation. Exercise capacity measured by predicted peak oxygen uptake (VO2%) and ventilatory expiratory slope (VE/CO2) is often impaired in EA and both are markers for mortality in adult congenital heart disease. Cardiovascular magnetic resonance (CMR) derived risk factors for adverse events (MACE) in unrepaired EA include reduced biventricular ejection fraction (EF) and low cardiac index. Whether and how these markers are modulated by TVR requires study. Purpose: We aimed to assess whether TVR modulates known markers of exercise intolerance and CMR risk factors for MACE in EA. Methods: Thirty-six consecutive EA adult (age≥16 years) patients (age at operation 37.4 ± 15.4 years, 13/12 ASD/PFO closures, 64% women) who underwent TV repair/replacement (15/21) between 2004-2014 and had pre-TVR CMR were retrospectively included. Twenty-four had CMR (in median 1.7 years) after TVR. Thirty-four had cardiopulmonary exercise test with VO2% and VE/CO2 prior to TVR, 23 one year and 17 five years after TVR. For CMR biventricular assessment, delineations were performed in short-axis cine stacks. Cardiac index was computed from velocity encoded phase contrast images from aortic flow. All volumes were indexed to body surface area. TR was graded none to severe (0-3). Results: Thirty patients were in NYHA class ≥2 pre-TVR, 10 at 1-year and 8 at 5-year post-TVR (Figure 1). Compared to pre-TVR, VO2% continued to increase 5 years post-TVR (60 ± 16% vs 72 ± 14%, p = 0.002), but was not significantly increased at 1-year post-TVR (69 ± 19%, p = 0.06). For VE/CO2, pre-TVR values (40 ± 15) were increased compared to 1-year post-TVR (33 ± 6, p = 0.02) but without further amelioration after 5 years (33 ± 6). Cardiac index increased (2.4 ± 0.7 vs 2.8 ± 0.5/min/m2, p = 0.02). However, RVEF decreased (52 ± 7 vs 46 ± 9%, p = 0.003) and LVEF remained unchanged (68 ± 8 vs 67 ± 8%, p = 0.3) after TVR. As expected, surgery reduced TR grade (median 3 vs 1.5), RVEDVi (174 ± 51 vs 109 ± 22ml/m2) and RV/LV ratio (2.9 ± 1.1 vs 1.7 ± 0.3, all p < 0.0001). Conclusions: TV surgery for Ebstein's anomaly clearly modulates known risk factors for adverse outcome and was associated with improved subjective and objective exercise tolerance early and mid-term after intervention. This may be due to the concurrent increase in cardiac index demonstrated by CMR and secondary to augmented LV end diastolic volume at a stable LVEF. These findings are suggestive of improved future freedom from MACE. But this needs testing including the degree to which the RVEF decline seen post-TVR mitigates potential benefits beyond symptoms. The improvement in VO2% continued for 5 years which indicates clinical improvement after TVR continues past the first year.